Desain dan Implementasi Sistem Pengelolaan Administrasi dan Keuangan Sekolah Taman Kanak-kanak - Oktariza, Melisa; Rochmawati, Rochmawati; Yuniar, Irna (Jurnal Telematika, 2018)
Early Childhood education, especially kindergarten (TK), plays an important role in the level of formal school education, thus requiring good school management standard. As a good school management standard, can be seen from administrative and financial management. During this time, the administrative and financial management processes at the XYZ Kindergarten school used several books that had been provided by the education office of government and also that school, which included student master books, teachers data, attendance lists, group mutations, incoming / outgoing letters, student development and financial records that enter and leave various operational activities of the school. Manual management through books causes data collection to occur, accumulated physical documents, and the need for time to search for the required documents, as well as the data synchronization process. In addition, parent meeting activities also require special recording, which has only been done on paper so that it is not well documented. For this reason, this study aims to design or built and implement a web-based system that can help kindergarten in managing administration and finance. The condition of the school was analyzed using rich picture and BPMN, built with SDLC work method in the form of prototype, designed using UML and ERD, programming using PHP with a framework that is CodeIgniter, as well as database using MySQL. This research is able to produce administrative data management such as student master book data, teachers data, attendance lists, incoming and outgoing mail, managing finances in the form of records of income transactions for operational activities of parents and school expenses, accounting records in the form of general journals, ledgers, and report on cash receipts and disbursements, as well as income statement.Pendidikan anak usia dini, khususnya sekolah taman kanak-kanak (TK), memegang peranan penting dalam jenjang pendidikan sekolah formal, sehingga membutuhkan standar pengelolaan sekolah yang baik. Salah satu bentuk standar pengelolaan sekolah yang baik dapat dilihat dari pengelolaan administrasi dan keuangan. Selama ini, proses pengelolaan administrasi dan keuangan di sekolah TK XYZ menggunakan beberapa buku yang sudah diberikan oleh dinas pendidikan maupun yang digunakan oleh sekolah, yang meliputi buku induk siswa, data pendidik, daftar hadir, mutasi kelompok, surat masuk/keluar, perkembangan peserta didik, serta catatan keuangan yang masuk dan keluar dari berbagai kegiatan operasional sekolah. Pengelolaan melalui buku menyebabkan terjadinya perulangan pendataan, dokumen fisik yang bertumpuk, dan perlunya waktu untuk mencari beberapa dokumen yang diperlukan, serta proses sinkronisasi data. Selain itu, kegiatan pertemuan orangtua juga memerlukan pencatatan khusus, yang selama ini hanya dilakukan di kertas, sehingga tidak terdokumentasikan dengan baik. Untuk itu, penelitian ini dibuat dengan tujuan untuk mendesain atau merancang dan mengimplementasikan sebuah sistem berbasis web yang dapat membantu sekolah TK dalam mengelola administrasi dan keuangan. Kondisi sekolah dianalisis menggunakan rich picture dan BPMN, dibangun dengan metode pengerjaan SDLC berupa prototype, didesain menggunakan UML dan ERD, pemrograman menggunakan PHP dengan framework yaitu CodeIgniter, serta basis data menggunakan MySQL. Penelitian ini mampu menghasilkan pengelolaan data administrasi seperti data buku induk siswa, data tenaga kependidikan, daftar hadir, surat masuk dan keluar, mengelola keuangan berupa catatan transaksi pemasukan kegiatan operasional dari para orangtua maupun pengeluaran sekolah, catatan akuntansi berupa jurnal umum, buku besar, serta laporan penerimaan dan pengeluaran kas, serta laporan laba rugi.